Конденсацiя ґраткового газу та її зв’язок з розбiжнiстю вiрiальних розкладiв за степенями активностi - Ushcats, M. V.; Bulavin, L. A.; Sysoev, V. M.; Ushcats, S. Yu. (Publishing house "Academperiodika", 2018)
An efficient algorithm for the calculation of high-order reducible cluster integrals on the basis of irreducible integrals (virial coefficients) has been proposed. The algorithm is applied to study the behavior of the well-known virial expansions of the pressure and density in power series of activity up to very high-order terms, as well as recently derived symmetric power expansions in the reciprocal activity, in the framework of a specific lattice gas model. Our results are consistent with those obtained in other modern studies of the partition function in terms of the density. They disclose the physical meaning of the divergence that the mentioned expansions demonstrate in the condensation region.